Eelgrass (Zostera marina) can tolerate salinity fluctuations - Katrin Rehlmeyer; Dindi Hiddink Verberne; Ellis J. Weinberg; Wilhelmina F. van Dorp; Maite L. Vogel; Oscar Franken; Hans van Veen; Han Olff; Tjisse van der Heide; Laura L. Govers (Journal of Experimental Marine Biology and Ecology, 2026)

Marine Benthic Community Assembly Is Taxonomically Stochastic but Functionally Deterministic in a Dynamic Coastal Sea - Milenka Sloots; Oscar Franken; Kasper J. Meijer; Tjisse van der Heide; Laura L. Govers; Han Olff (Ecology Letters, 2025)
Understanding the balance between deterministic and stochastic processes in community assembly is crucial for interpreting ecological community dynamics. Moreover, it provides perspective for conservation and management actions, as deterministic processes can be subject to targeted interventions, but stochastic processes are less manageable. Through a spatially explicit macrozoobenthic monitoring campaign consisting of 1323 sampling locations in the Dutch Wadden Sea, we examined the relative importance of deterministic and stochastic processes, including the role of hydrodynamic disturbance gradients. We found species‐based community assembly to be mainly driven by stochastic processes, while trait‐based assembly was more deterministic and environmentally driven. Environmental disturbance levels minimally affected the relative importance of stochastic and deterministic processes. For coastal benthic ecosystems, we therefore recommend management actions to target specific desired functional groups rather than specific changes in community composition.

Reconstructing historical catch trends of threatened sharks and rays based on fisher ecological knowledge - Guido Leurs; Rima W. Jabado; Assana Camará; Lilísio Dos Santos; Diosnes Manuel Nonque; Thije J. Zuidewind; Iça Barry; Pierre Campredon; Benja Blaschke; Karin de Boer; Nadia Hijner; Han Olff; et al. (Conservation Biology, 2025)
Small‐scale fisheries often lack historical shark and ray catch information, hampering their management. We reconstructed historical catch trends and current fishing pressure by combining local ecological knowledge, satellite‐based vessel counts, and a short‐term landing‐site survey. To test the effectiveness of this method, we focused on the Bijagós Archipelago (Guinea‐Bissau, West Africa), where historical fisheries data are lacking. Benthic rays (stingrays [Dasyatidae] and butterfly rays [ Gymnura spp.]), benthopelagic rays (duckbill eagle rays [ Aetomylaeus bovinus ] and cownose rays [ Rhinoptera marginata ]), guitarfish ( Glaucostegus and Rhinobatos spp.), requiem sharks (Carcharhinidae), and hammerhead sharks ( Sphyrna spp.) declined in abundance by 81.5–96.7% (species dependent) from 1960 to 2020. Fishing effort increased annually: fishing trip duration by 42.0% (SE 3.4), numbers of fishing vessels at sea as perceived by fishers by 36.3% (1.0) (1960–2020), and number of vessels by 12.0% (1.1) (2007–2022). We estimated that in 2020, fishing vessels collectively captured 61–264 sharks and 522–2194 rays per day in the archipelago, depending on the proportion of the fishing fleet that was active (i.e., low fleet activity of 18% and high fleet activity of 80%). We advocate for reducing shark and ray catches by regulating fleet size, reinforcing boundaries of protected areas, and collecting fisher‐dependent information on shark and ray landings to safeguard these vulnerable species and coastal livelihoods. We demonstrated the effectiveness of using this 3‐pronged approach to provide baseline data on shark fisheries, a common challenge in areas with small‐scale fisheries and limited research capacity.

Overfishing of Threatened Bycatch Species in a Marine Protected Area: The Elasmobranchs of Banc d'Arguin, Mauritania - Sidi Yahya Cheikhna Lemrabott; Anieke van Leeuwen; Guido Leurs; El‐Hacen Mohamed El‐Hacen; Theunis Piersma; Amadou Abdarahmane Sall; Ebaye Sidina; Lemhaba Yarba; Han Olff (Fisheries Management and Ecology, 2025)
Elasmobranch (rays and sharks) populations are vulnerable to overexploitation due to their slow growth, late maturity, and low fecundity. Industrial fishery impacts on sharks and rays are known, whereas impacts of artisanal fisheries are less understood. We quantified catches of sharks and rays in artisanal fisheries at the Parc National du Banc d'Arguin (Banc d'Arguin), Mauritania (West Africa) during 1998–2020, a period when fishing effort increased around 2006, catches increased, but catch‐per‐unit‐effort declined substantially. Shark nets and meagre fixed gill nets were used to catch elasmobranchs, with catches comprising over 60% of elasmobranch species. Therefore, elasmobranchs were not bycatch, but rather, the target of fisheries. Of 33 elasmobranch species captured, 94% of shark species and 76% of ray species are threatened with extinction. We recommend that management approaches should focus on fishing locations with the highest occurrence of threatened elasmobranch species in catches, through new regulations on fishing gear types and discouragement of trade in elasmobranch products from Banc d'Arguin.

Unraveling the drivers of forage quality variation in the Serengeti - Yuhong Li; Sanne Piek; Emilian P. Mayemba; Kelvin R. Shoo; Michiel P. Veldhuis; Han Olff (Ecology, 2025)
Variation in forage quality is a key dimension of herbivore resource partitioning, but the main determinants of such variation across environmental gradients remain poorly understood. It is especially unclear how much variation in plant nutrient contents and stoichiometry is driven by plant species turnover versus by intraspecific variation across sites. We investigated variation in forage quality across nine sites along a key environmental gradient of increasing rainfall and decreasing soil fertility in the Serengeti National Park, Tanzania. We compared leaf elemental contents of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sodium (Na) and three nutrient ratios (N:P, Ca:P, and K:Na) between sites, between species within the same site, and between sites within the same species. Site‐average N, P, and K leaf contents decreased with increasing rainfall and decreasing soil fertility. The decline in N and K was primarily associated with species turnover, with their contents remaining relatively stable within species. The decline in P was associated with a combination of species turnover and intraspecific variation, with intraspecific P content decreasing strongly with increasing rainfall (decreasing soil fertility) across sites. Variation in site‐average Ca, Mg, and Na leaf contents did not significantly correlate with rainfall or soil fertility and was mainly explained by species turnover between sites. Comparing leaf nutrient content and ratios to literature‐derived nutritional requirements for large herbivores suggests that Na is severely limiting in this ecosystem. K seems sufficient everywhere, and the other elements are moderately limiting. If Serengeti herbivores rely on plants for their nutrient intake and are nutrient‐limited, these results suggest herbivores with high N, Ca, or Mg requirements should optimize their diet by selecting particular species, relatively independent of sites. Herbivores with a high P requirement can instead best select particular sites, relatively independent of plant species. To obtain sufficient Na, herbivores can target particular species at particular sites. Thus, resource partitioning among Serengeti herbivores may occur at different levels for different elements. Interspecific variation in herbivore nutrient requirements would then drive resource partitioning both across sites (for P and Na) and between plant species (N, Ca, Mg, and Na).

Synthesis of Population Trends Reveals Seascape‐Wide Reorganisation of Biodiversity From Microalgae to Birds - Anika Happe; Kasper J. Meijer; Jan‐Claas Dajka; Oscar Franken; Holger Haslob; Laura L. Govers; Michael Kleyer; Annebelle C. M. Kok; Lucie Kuczynski; Kertu Lõhmus; Sancia E. T. van der Meij; Han Olff; et al. (Global Change Biology, 2025)
Many monitoring programs aim to understand regional biodiversity patterns in relation to global and regional conservation targets, using either community‐wide biodiversity metrics to describe the community status or trends of pre‐selected “key” species as biodiversity change indicators. However, the former often lacks information on which species are changing, and the latter is heavily skewed towards specific taxa, potentially overlooking changes in other, functionally important taxa. We gathered an extensive set of monitoring data with over 3000 population trends (ranging from 5 to 91 years in duration) for a wide range of taxa across the Wadden Sea. We combined a systematic and quantitative categorization of population trends (weighted vote count) with a meta‐analysis on different taxonomic levels. This allowed the first cross‐taxa synopsis of species declines and increases and determined their directionalities throughout time. Our meta‐analysis showed an overall decrease in population size for fish, zooplankton, and plant species, while birds showed an overall increase. However, these increases mask recent negative trends within specific bird groups since the late 1990s. In contrast, fish populations exhibited declines over the entire monitoring period. Species with declining populations (losers) were phylogenetically related, whereas species with increasing populations (winners) represented various organismal groups. Directionality and onsets of change in population trends were temporally synchronized throughout several groups, such as bivalves, fish, and birds, and may provide warning signals for future local extinctions in these taxa. Our analysis moves beyond typical indicator species by including the entire species inventory of the system. Basal trophic levels of aquatic ecosystems, such as zooplankton and phytoplankton, are often missing from policy assessments but are among the most important organism groups for ecosystem functioning. Here, we show that without additional monitoring effort, a systematic analysis of population trends adds to our understanding of trophic and compositional restructuring of ecosystems.

Bioturbation by Benthic Stingrays Alters the Biogeomorphology of Tidal Flats - Janne Nauta; Guido Leurs; Brian O. Nieuwenhuis; Donné R. A. H. Mathijssen; Han Olff; Tjeerd J. Bouma; Daphne van der Wal; Nadia Hijner; Aissa Regalla; Samuel Ledo Pontes; Laura L. Govers (Ecosystems, 2024)
Fishing-down-marine-food-webs has resulted in alarming declines of various species worldwide. Benthic rays are one examples of such overexploited species. On tidal flats, these rays are highly abundant and play an ecologically important role. They use tidal flats as refuge, feeding and resting grounds, during which they bury into the sediment, which results in sediment bioturbation. Changes in bioturbation intensity, following ray removal, may affect the biogeomorphology of tidal flats with possible cascading effects on the macrozoobenthic community. However, it is poorly understood how these indirect effects could influence ecosystem function. We therefore studied the geomorphic impact of benthic rays (specifically the pearl whipray/stingray Fontitrygon margaritella ) on the tropical tidal flats of the Bijagós Archipelago, Guinea-Bissau, on a landscape scale. We investigated 1) bioturbation rates by rays using drone and ground surveys, 2) the spatial distribution of ray pits on multiple tidal flats, 3) the impact of rays on sediment properties and macrozoobenthos by experimental exclusion (15 months). Benthic rays bioturbated 3.7 ± 0.35% of the tidal flat’s sediment surface per day over one single 24-h period, which equals a complete top-sediment-surface turnover every 27 days. The spatial distribution of ray pits was affected by tidal flat geomorphology since pits decayed faster at areas exposed to strong hydrodynamic forces. Predator exclusion altered sediment properties, leading to changes in sedimentation (− 17%) and erosion (− 43%) rates. In addition, macrozoobenthic species composition changed, marked by an increase in Capitellidae worms and a greater biomass of Malacostraca over time. These changes indicated substantial effects of ray bioturbation on the biotic and geomorphic landscape of tidal flats. Overall, we conclude that changing abundances of benthic rays can have clear landscape-wide geomorphological effects on intertidal ecosystems. These indirect consequences of fisheries should be incorporated in integrative management plans to preserve tidal flats and connected ecosystems.

Reintroduction of self-facilitating feedbacks could advance subtidal eelgrass (Zostera marina) restoration in the Dutch Wadden Sea - Katrin Rehlmeyer; Oscar Franken; Tjisse van der Heide; Sander J. Holthuijsen; Kasper J. Meijer; Han Olff; Wouter Lengkeek; Karin Didderen; Laura L. Govers (Frontiers in Marine Science, 2024)
Extensive subtidal eelgrass ( Zostera marina ) meadows (~150 km 2 ) once grew in the Dutch Wadden Sea, supporting diverse species communities, but disappeared in the 1930s and have been absent ever since. Identifying the most critical bottlenecks for eelgrass survival is a crucial first step for reintroduction through active restoration measures. Seagrasses are ecosystem engineers, inducing self-facilitating feedbacks that ameliorate stressful conditions. Consequently, once seagrass, including its self-facilitating feedbacks, is lost, reintroduction can be challenging. Therefore, we aimed to test whether 1) sediment stabilization and 2) hydrodynamic stress relief would facilitate eelgrass survival in a field experiment replicated at two sites in the Dutch Wadden Sea. We induced feedbacks using biodegradable root-mimicking structures (BESE-elements) and sandbag barriers. Root mimics had a significant positive effect, increasing the chances of short-term survival by +67% compared to controls. Contrary to our expectations, barriers decreased short-term survival probabilities by -26%, likely due to hydrodynamic turbulence created by the barrier edges, leading to high erosion rates (-14 cm). Site selection proved crucial as short-term survival was entirely negated on one of the two study sites after five weeks due to high floating and epiphytic macroalgae loads. No long-term survival occurred, as plants died at the other site two weeks later. Overall, we found that sediment stabilization by root-mimicking structures was promising, whereas manipulating hydrodynamic forces using sandbag barriers had adverse effects. A mechanistic understanding of transplant failures is required before attempting large-scale restoration. Our study indicates that for seagrass restoration in the Wadden Sea, one should carefully consider 1) the reintroduction of positive feedbacks through restoration tools, 2) donor population choice and transplantation timing, and 3) site selection based on local biotic and abiotic conditions. Optimizing these restoration facets might lower additive stress to a degree that allows long-term survival.

Mutual facilitation between foundation species Mytilus edulis and Lanice conchilega promotes habitat heterogeneity on tidal flats - Janne Nauta; Kasper J. Meijer; Lissie W. de Groot; Valérie C. Reijers; Tjeerd J. Bouma; Daphne van der Wal; Han Olff; Sander J. Holthuijsen; Allert I. Bijleveld; Henk W. van der Veer; Oscar Franken; Laura L. Govers (Frontiers in Marine Science, 2024)
Foundation species that modify their habitat can facilitate other species, including other foundation species. Most studies focus solely on a single foundation species, overlooking such facilitation cascades. In this study, we investigated the interactions between the two coastal foundation species Mytilus edulis (blue mussel) and Lanice conchilega (sand mason worm). We investigated whether these species engage in facilitative interactions or if their association simply reflects a shared ecological niche on the soft-sediment intertidal flats of the Dutch Wadden Sea. To do so, we performed species distribution modeling, manipulative field experiments, and field surveys. We found a positive association between both foundation species, with a 2.45 times higher occurrence of both species compared to a random distribution. In addition, these species partially occupied the same ecological niche. We demonstrated that L. conchilega provided settlement substrate for M. edulis spat, increasing densities by 400 times compared to bare plots. Furthermore, M. edulis reefs facilitated L. conchilega occurrence in the wake of the reef. Biogenic reef development revealed that this interspecific facilitation resulted in spatial habitat heterogeneity. Therefore, we conclude that interspecific facilitation can significantly enhance the occurrence of these two important intertidal foundation species. Acknowledgment of such complex facilitation interactions has an untapped potential for improving the success of restoration and conservation programs.

Where land meets sea: Intertidal areas as key‐habitats for sharks and rays - Guido Leurs; Brian O. Nieuwenhuis; Thije J. Zuidewind; Nadia Hijner; Han Olff; Laura L. Govers (Fish and Fisheries, 2023)
Intertidal habitats (i.e. marine habitats that are (partially) exposed during low tide) have traditionally been studied from a shorebird‐centred perspective. We show that these habitats are accessible and important to marine predators such as elasmobranchs (i.e. sharks and rays). Our synthesis shows that at least 43 shark and 45 ray species, of which 54.5% are currently threatened, use intertidal habitats. Elasmobranchs use intertidal habitats mostly for feeding and as refugia, but also for parturition and thermoregulation. However, the motivation of intertidal habitat use remains unclear due to limitations to observe elasmobranch behaviour in these dynamic habitats. We argue that elasmobranch predators can play an important role in intertidal food webs by feeding on shared resources during high tide (i.e. ‘high‐tide predators’), which are accessible and also consumed by terrestrial or avian predators during low tide (i.e. ‘low‐tide predators’). In addition, elasmobranchs are able to change the bio‐geomorphology of intertidal habitats by increasing habitat heterogeneity due to feeding activities and may also alter resource availability for other consumers. We discuss how the ecological role of elasmobranchs in intertidal habitats is being affected by the continued overexploitation of these species, and conversely, how the global loss of intertidal areas poses an additional threat to an already vulnerable taxonomic group. We conclude that studies on intertidal ecology should include both low‐tide (e.g. shorebirds) and high‐tide (e.g. elasmobranchs) predatory guilds and their ecological interactions. The global loss of elasmobranch predatory species and intertidal habitat provides additional compelling arguments for the conservation of these areas.

The metamicrobiome: key determinant of the homeostasis of nutrient recycling - Inger K. de Jonge; Michiel P. Veldhuis; J. Hans C. Cornelissen; Matty P. Berg; Han Olff (Trends in Ecology & Evolution, 2023)

Fossilized diatoms as indirect indicators of the origin of carbon stored in intertidal flats - El-Hacen M. El-Hacen; Ties Mens; Tjeerd J. Bouma; Theunis Piersma; Suzanne A.G. Leroy; Han Olff; Francesca Sangiorgi (Frontiers in Marine Science, 2022)
Coastal systems store enormous carbon quantities in their sediment, which originates from various autochthonous and allochthonous sources. Carbon fluxes in coastal ecosystems have a strong effect on the recipient food-webs and carbon emission offsets. Yet, the relative importance of autochthonous vs. allochthonous C inputs to coastal carbon budget is still challenging to identify. Here, we combine diatoms preserved in the sediment with geochemical analyses to identify the sources of carbon stored in Africa’s largest intertidal seagrass beds at Banc d’Arguin, Mauritania. The area lies between an active ocean upwelling and the ‘Sahara-dust hotspot’ systems. The extensive seagrass beds of the area are thus expected to receive C from these neighboring systems in addition to producing C in-situ . Three sediment cores (50 cm) were collected at three intertidal sites with different hydrodynamic regimes, and analyzed for diatom composition, total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), and carbon isotopic signatures (δ 13 C). Diatom taxa are grouped into three guilds: (1) benthic (epiphyte, epipelon, and epipsammon), (2) planktonic, and (3) freshwater. Benthic diatoms are considered to be autochthonous, while typical oceanic and freshwater diatoms are considered to be allochthonous. Benthic diatoms are the most diverse and abundant group, while allochthonous freshwater (i.e., dust imported) and typical upwelling (i.e., tidal imported) taxa ranked last in both abundance and species’ richness. Structure equation modelling shows that variation in the stored carbon is best explained by the total abundance of diatoms and guild composition. We conclude that the C stored in the intertidal seagrass beds of Banc d’Arguin is predominantly autochthonous. Our method provides an effective way to identify historical carbon sources in coastal systems.

Potential Micro-Plastics Dispersal and Accumulation in the North Sea, With Application to the MSC Zoe Incident - Johan van der Molen; Sonja M. van Leeuwen; Laura L. Govers; Tjisse van der Heide; Han Olff (Frontiers in Marine Science, 2021)
The fate and effects of microplastics in the marine environment are an increasingly important area of research, policy and legislation. To manage and reduce microplastics in the seas and oceans, and to help understand causes and effects, we need improved understanding of transport patterns, transit times and accumulation areas. In this paper, we use a particle tracking model to investigate the differences in dispersal and accumulation of microplastics with different properties (floating and sinking) in the North Sea. In these simulations, particles were released with a uniform horizontal distribution, and also from rivers at rates proportional to the river runoff. The results showed that floating particles can accumulate temporarily on salinity fronts and in gyres, and are deposited predominantly on west-facing beaches. Sinking particles moved more slowly and less far, accumulated in deeper areas associated with fine sediments, and were deposited more on west- and north-facing beaches. The model was also applied to the MSC Zoe incident of 1 January 2019, in which 342 containers were lost north of the Dutch Wadden islands in the southern North Sea, tracking two types of microplastics with similar properties (∼5mm floating HDPE pellets and ∼0.6mm sinking PS grains) to identify release locations and potential accumulation areas. We used field observations collected by a citizen science initiative ( waddenplastic.nl ) to constrain the model results. For these simulations, particles were released along the ship’s trajectory and at locations on the trajectory where debris was found. The simulations of the MSC Zoe incident showed that over 90% of floating (∼5mm) HDPE pellets beached within 3–7 weeks, and predominantly on the more eastern Dutch Wadden Islands in agreement with the field observations, and that most of the sinking (∼0.6mm) PS grains were still at sea after 6 weeks, and a large proportion may have been deposited on German shores. The work is relevant to Descriptor 10 (Marine Litter) of the EU Marine Strategy Framework Directive.

Conservation Implications of Sabellaria spinulosa Reef Patches in a Dynamic Sandy-Bottom Environment - Karin J. van der Reijden; Leo Koop; Sebastiaan Mestdagh; Mirjam Snellen; Peter M. J. Herman; Han Olff; Laura L. Govers (Frontiers in Marine Science, 2021)
Biogenic reefs form biodiversity hotspots and are key components of marine ecosystems, making them priority habitats for nature conservation. However, the conservation status of biogenic reefs generally depends on their size and stability. Dynamic, patchy reefs may therefore be excluded from protection. Here, we studied epibenthos and epifauna density, richness, and community composition of patchy, dynamic Sabellaria spinulosa (ross worm) reefs in the North Sea. This study was conducted by comparing boxcore (endobenthos) and video transect (epifauna) data from two research campaigns in 2017 and 2019 to the Brown Bank area on the Dutch Continental Shelf, where S. spinulosa reefs were first discovered in 2017. The Brown Bank area is characterized by dynamic, migratory bedforms at multiple scales which potentially affect biogenic reef stability. We showed that S. spinulosa habitats had a patchy distribution and alternated with habitats comprised of plain sand. Average S. spinulosa habitat patch size was 5.57 ± 0.99 m and 3.94 ± 0.22 m in 2017 and 2019, respectively (mean ± SE), which especially in 2019 closely resembled the small-scale megaripple bedforms. Contrary to the endobenthos communities that were unaffected by S. spinulosa , epifauna density and species richness were at least two times higher in S. spinulosa habitats compared to sandy habitats, resulting in different community compositions between the two habitat types. We showed that S. spinulosa persisted in the area for almost 2 years. Although the stability of individual patches remained unclear, we demonstrated that even patchy biogenic reefs may promote density and local biodiversity of mobile, epibenthic species, very likely as a result of increased habitat heterogeneity provided by reef habitat patches. This indicates that patchy biogenic reefs that occur in dynamic environments may also have high ecological value and their conservation status should be (re)considered to ensure their protection.

Industrial Fishing Near West African Marine Protected Areas and Its Potential Effects on Mobile Marine Predators - Guido Leurs; Karin J. van der Reijden; Sidi Yahya Cheikhna Lemrabott; Iça Barry; Diosnes Manuel Nonque; Han Olff; Samuel Ledo Pontes; Aissa Regalla; Laura L. Govers (Frontiers in Marine Science, 2021)
Marine Protected Areas (MPAs) are increasingly implemented to facilitate the conservation of marine biodiversity and key habitats. However, these areas are often less effective to conserve mobile marine species like elasmobranchs (i.e., sharks and rays). Industrial fishing near MPA borders possibly impacts vulnerable species utilizing these protected areas. Hence, we aimed to study spatiotemporal patterns of industrial fisheries near MPAs, in relation to the bycatch of elasmobranchs. Specifically, we analyzed the spatiotemporal fishing effort within the West African region, mapped fishing effort in the direct vicinity of the Parc National du Banc d’Arguin (PNBA, Mauritania) and the Bijagós Archipelago (BA, Guinea Bissau), and compared the seasonal overlap between elasmobranch bycatch and fishing effort near these MPAs. We combined Automatic Identification System (AIS) data and local fisheries observer data, and determined fishing effort for each gear type and compared this with bycatch of elasmobranchs. We found that industrial fishing effort was dominated by trawling, drifting longlines, and fixed gear types. Although no industrial fishing was observed within both MPAs, 72 and 78% of the buffer zones surrounding the MPAs were fished for the Banc d’Arguin and Bijagós, respectively. Within the Banc d’Arguin buffer zone, trawling and drifting longlines dominated, with longlines mainly being deployed in fall. In the Bijagós buffer zone, trawling and fixed gears were most prevalent. Fisheries observer data for Mauritania showed that elasmobranch catches increased during the most recent sampling years (2016–2018). Elasmobranch catches within the waters of Guinea Bissau peaked in 2016 and decreased in the following two years. Seasonal patterns in elasmobranch bycatch within the waters of both countries are likely caused by increased catches of migratory species. Catches of rays peaked in May and June for Mauritania, and in October for Guinea Bissau. Shark catches were highest in February and July in Mauritanian waters, and in May and October in the waters of Guinea Bissau. Our study indicates that industrial fisheries near the border of ecologically important MPAs may have potentially major implications for ecosystem functioning by the removal of (migratory) predatory species.

Ontogenetic niche shifts as a driver of seasonal migration - Wimke Fokkema; Henk P. van der Jeugd; Thomas K. Lameris; Adriaan M. Dokter; Barwolt S. Ebbinge; André M. de Roos; Bart A. Nolet; Theunis Piersma; Han Olff (Oecologia, 2020)
Ontogenetic niche shifts have helped to understand population dynamics. Here we show that ontogenetic niche shifts also offer an explanation, complementary to traditional concepts, as to why certain species show seasonal migration. We describe how demographic processes (survival, reproduction and migration) and associated ecological requirements of species may change with ontogenetic stage (juvenile, adult) and across the migratory range (breeding, non-breeding). We apply this concept to widely different species (dark-bellied brent geese ( Branta b. bernicla ), humpback whales ( Megaptera novaeangliae ) and migratory Pacific salmon ( Oncorhynchus gorbuscha ) to check the generality of this hypothesis. Consistent with the idea that ontogenetic niche shifts are an important driver of seasonal migration, we find that growth and survival of juvenile life stages profit most from ecological conditions that are specific to breeding areas. We suggest that matrix population modelling techniques are promising to detect the importance of the ontogenetic niche shifts in maintaining migratory strategies. As a proof of concept, we applied a first analysis to resident, partial migratory and fully migratory populations of barnacle geese ( Branta leucopsis ). We argue that recognition of the costs and benefits of migration, and how these vary with life stages, is important to understand and conserve migration under global environmental change.

Seagrass Sensitivity to Collapse Along a Hydrodynamic Gradient: Evidence from a Pristine Subtropical Intertidal Ecosystem - El-Hacen M. El-Hacen; Tjeerd J. Bouma; Laura L. Govers; Theunis Piersma; Han Olff (Ecosystems, 2019)

Unexpected dietary preferences of Eurasian Spoonbills in the Dutch Wadden Sea: spoonbills mainly feed on small fish not shrimp - Jeltje Jouta; Petra de Goeij; Tamar Lok; Estefania Velilla; Cornelis J. Camphuysen; Mardik Leopold; Henk W. van der Veer; Han Olff; Otto Overdijk; Theunis Piersma (Journal of Ornithology, 2018)

Herbivore exclusion promotes a more stochastic plant community assembly in a natural grassland - Juan Alberti; Elisabeth S. Bakker; Roel van Klink; Han Olff; Christian Smit (Ecology, 2017)
Both bottom‐up (e.g., nutrients) and top‐down (e.g., herbivory) forces structure plant communities, but it remains unclear how they affect the relative importance of stochastic and deterministic processes in plant community assembly. Moreover, different‐sized herbivores have been shown to have contrasting effects on community structure and function, but their effects on the processes governing community assembly (i.e., how they generate the impacts on structure) remain largely unknown. We evaluated the influence of bottom‐up and top‐down forces on the relative importance of deterministic and stochastic processes during plant community assembly. We used the data of a 7‐yr factorial experiment manipulating nutrient availability (ambient and increased) and the presence of vertebrate herbivores (>1 kg) of different body size in a floodplain grassland in The Netherlands. We used a null model that describes a community composition expected by chance (i.e., stochastic assembly) and compared the plant community composition in the different treatments with this null model (the larger the difference, the more deterministically assembled). Our results showed that herbivore exclusion promoted a more stochastic plant community assembly, whereas increased nutrients played a relatively minor role in determining the relative importance of stochasticity in community assembly. Large herbivores facilitated intermediate‐sized mammal herbivores, resulting in synergistic effects of enhanced grazing pressure and a more deterministic and convergent plant community assembly. We conclude that herbivores can act as strong deterministic forces during community assembly in natural systems. Our results also reveal that although large‐ and intermediate‐sized mammal herbivores often have contrasting effects on many community and ecosystem properties, they can also synergistically homogenize plant communities.

Termites promote resistance of decomposition to spatiotemporal variability in rainfall - Michiel P. Veldhuis; Francisco J. Laso; Han Olff; Matty P. Berg (Ecology, 2017)
The ecological impact of rapid environmental change will depend on the resistance of key ecosystems processes, which may be promoted by species that exert strong control over local environmental conditions. Recent theoretical work suggests that macrodetritivores increase the resistance of African savanna ecosystems to changing climatic conditions, but experimental evidence is lacking. We examined the effect of large fungus‐growing termites and other non‐fungus‐growing macrodetritivores on decomposition rates empirically with strong spatiotemporal variability in rainfall and temperature. Non‐fungus‐growing larger macrodetritivores (earthworms, woodlice, millipedes) promoted decomposition rates relative to microbes and small soil fauna (+34%) but both groups reduced their activities with decreasing rainfall. However, fungus‐growing termites increased decomposition rates strongest (+123%) under the most water‐limited conditions, making overall decomposition rates mostly independent from rainfall. We conclude that fungus‐growing termites are of special importance in decoupling decomposition rates from spatiotemporal variability in rainfall due to the buffered environment they create within their extended phenotype (mounds), that allows decomposition to continue when abiotic conditions outside are less favorable. This points at a wider class of possibly important ecological processes, where soil‐plant‐animal interactions decouple ecosystem processes from large‐scale climatic gradients. This may strongly alter predictions from current climate change models.

Grassland structural heterogeneity in a savanna is driven more by productivity differences than by consumption differences between lawn and bunch grasses - Michiel P. Veldhuis; Heleen F. Fakkert; Matty P. Berg; Han Olff (Oecologia, 2016)

The Importance of Coprophagous Macrodetritivores for the Maintenance of Vegetation Heterogeneity in an African Savannah - Ruth A. Howison; Matty P. Berg; Christian Smit; Kaylee van Dijk; Han Olff (Ecosystems, 2016)

Indirect interactions among tropical tree species through shared rodent seed predators: a novel mechanism of tree species coexistence - Carol X. Garzon‐Lopez; Liliana Ballesteros‐Mejia; Alejandro Ordoñez; Stephanie A. Bohlman; Han Olff; Patrick A. Jansen (Ecology Letters, 2015)
The coexistence of numerous tree species in tropical forests is commonly explained by negative dependence of recruitment on the conspecific seed and tree density due to specialist natural enemies that attack seeds and seedlings (‘Janzen–Connell’ effects). Less known is whether guilds of shared seed predators can induce a negative dependence of recruitment on the density of different species of the same plant functional group. We studied 54 plots in tropical forest on Barro Colorado Island, Panama, with contrasting mature tree densities of three coexisting large seeded tree species with shared seed predators. Levels of seed predation were far better explained by incorporating seed densities of all three focal species than by conspecific seed density alone. Both positive and negative density dependencies were observed for different species combinations. Thus, indirect interactions via shared seed predators can either promote or reduce the coexistence of different plant functional groups in tropical forest.

A new modeling approach estimates the relative importance of different community assembly processes - Fons van der Plas; Thijs Janzen; Alejandro Ordonez; Wimke Fokkema; Josephine Reinders; Rampal S. Etienne; Han Olff (Ecology, 2015)
The relative importance of niche‐based (e.g., competitive or stress‐based) and stochastic (e.g., random dispersal) processes in structuring ecological communities is frequently analyzed by studying trait distributions of co‐occurring species. While filtering processes, such as the exclusion of stress‐intolerant species from particular habitats, increase the trait similarity between co‐occurring species, other processes, such as resource competition, can limit the similarity of co‐occurring species. Comparing the observed trait distribution patterns in communities to null expectations from randomized communities (e.g., a draw of the same observed richness from the regional pool) therefore gives a first indication of the dominant process driving community assembly. However, such comparisons do not inform us about the relative contribution of these different processes in shaping community compositions in case of their joint operation (a likely scenario). Using an Approximate Bayesian Computation approach, we develop a new method that allows inference of the relative importance of dispersal, filtering, and limiting similarity processes for the assembly of observed communities with known species and trait composition. We applied this approach to a tree community data set, collected across 20 plots along strong rainfall and fire gradients in a South African savanna. Based on comparisons with simulations, we find that our new approach is powerful in identifying which community assembly scenario has the highest probability to generate the observed trait distribution patterns, while traditional null model comparisons perform poorly in detecting signs of limiting similarity. For the studied savanna tree communities, our analysis yields that dispersal processes are most important in shaping the functional trait distribution patterns. Furthermore, our models indicate that filtering processes were relatively most important in areas with high fire frequencies, while limiting similarity processes were relatively most important in areas with low fire frequency and high rainfall. We conclude that our new method is a promising improvement on current approaches to estimate the relative importance of community assembly processes across different species groups, ecosystems, and biomes. Future model modifications (e.g., the inclusion of individual‐based processes) could provide further steps in uncovering the underlying assembly processes behind observed community patterns.

Mesoherbivores affect grasshopper communities in a megaherbivore-dominated South African savannah - Fons van der Plas; Han Olff (Oecologia, 2014)

Generalities in grazing and browsing ecology: using across-guild comparisons to control contingencies - Johan T. du Toit; Han Olff (Oecologia, 2014)

Non-trophic Interactions Control Benthic Producers on Intertidal Flats - Serena Donadi; Joëlle Westra; Ellen J. Weerman; Tjisse van der Heide; Els M. van der Zee; Johan van de Koppel; Han Olff; Theunis Piersma; Henk W. van der Veer; Britas Klemens Eriksson (Ecosystems, 2013)

Responses of savanna lawn and bunch grasses to water limitation - Fons van der Plas; Patricia Zeinstra; Michiel Veldhuis; Rienk Fokkema; Elske Tielens; Ruth Howison; Han Olff (Plant Ecology, 2013)

Food Web Assembly at the Landscape Scale: Using Stable Isotopes to Reveal Changes in Trophic Structure During Succession - Maarten Schrama; Jeltje Jouta; Matty P. Berg; Han Olff (Ecosystems, 2013)

Herbivore trampling as an alternative pathway for explaining differences in nitrogen mineralization in moist grasslands - Maarten Schrama; Pieter Heijning; Jan P. Bakker; Harm J. van Wijnen; Matty P. Berg; Han Olff (Oecologia, 2013)

Cross‐habitat interactions among bivalve species control community structure on intertidal flats - Serena Donadi; Tjisse van der Heide; Els M. van der Zee; Johan S. Eklöf; Johan van de Koppel; Ellen J. Weerman; Theunis Piersma; Han Olff; Britas Klemens Eriksson (Ecology, 2013)
Increasing evidence shows that spatial interactions between sedentary organisms can structure communities and promote landscape complexity in many ecosystems. Here we tested the hypothesis that reef‐forming mussels ( Mytilus edulis L.), a dominant intertidal ecosystem engineer in the Wadden Sea, promote abundances of the burrowing bivalve Cerastoderma edule L. (cockle) in neighboring habitats at relatively long distances coastward from mussel beds. Field surveys within and around three mussel beds showed a peak in cockle densities at 50–100 m toward the coast from the mussel bed, while cockle abundances elsewhere in the study area were very low. Field transplantation of cockles showed higher survival of young cockles (2–3 years old) and increased spat fall coastward of the mussel bed compared to within the bed and to areas without mussels, whereas growth decreased within and coastward of the mussel bed. Our measurements suggest that the observed spatial patterns in cockle numbers resulted from (1) inhibition effects by the mussels close to the beds due to preemptive algal depletion and deteriorated sediment conditions and (2) facilitation effects by the mussels farther away from the beds due to reduction of wave energy. Our results imply that these spatial, scale‐dependent interactions between reef‐forming ecosystem engineers and surrounding communities of sedentary benthic organisms can be an important determinant of the large‐scale community structure in intertidal ecosystems. Understanding this interplay between neighboring communities of sedentary species is therefore essential for effective conservation and restoration of soft‐bottom intertidal communities.

Hippopotamus and livestock grazing: influences on riparian vegetation and facilitation of other herbivores in the Mara Region of Kenya - Erustus M. Kanga; Joseph O. Ogutu; Hans-Peter Piepho; Han Olff (Landscape and Ecological Engineering, 2013)

Seagrass–Sediment Feedback: An Exploration Using a Non-recursive Structural Equation Model - Eelke O. Folmer; Matthijs van der Geest; Erik Jansen; Han Olff; T. Michael Anderson; Theunis Piersma; Jan A. van Gils (Ecosystems, 2012)

Testing the metabolic theory of ecology - Charles A. Price; Joshua S Weitz; Van M. Savage; James Stegen; Andrew Clarke; David A. Coomes; Peter S. Dodds; Rampal S. Etienne; Andrew J. Kerkhoff; Katherine McCulloh; Karl J. Niklas; Han Olff; et al. (Ecology Letters, 2012)
The metabolic theory of ecology (MTE) predicts the effects of body size and temperature on metabolism through considerations of vascular distribution networks and biochemical kinetics. MTE has also been extended to characterise processes from cellular to global levels. MTE has generated both enthusiasm and controversy across a broad range of research areas. However, most efforts that claim to validate or invalidate MTE have focused on testing predictions. We argue that critical evaluation of MTE also requires strong tests of both its theoretical foundations and simplifying assumptions. To this end, we synthesise available information and find that MTE's original derivations require additional assumptions to obtain the full scope of attendant predictions. Moreover, although some of MTE's simplifying assumptions are well supported by data, others are inconsistent with empirical tests and even more remain untested. Further, although many predictions are empirically supported on average, work remains to explain the often large variability in data. We suggest that greater effort be focused on evaluating MTE's underlying theory and simplifying assumptions to help delineate the scope of MTE, generate new theory and shed light on fundamental aspects of biological form and function.

Ecosystem assembly rules: the interplay of green and brown webs during salt marsh succession - Maarten Schrama; Matty P. Berg; Han Olff (Ecology, 2012)
Current theories about vegetation succession and food web assembly are poorly compatible, as food webs are generally viewed to be static, and succession is usually analyzed without the inclusion of higher trophic levels. In this study we present results from a detailed analysis of ecosystem assembly rules over a chronosequence of 100 years of salt marsh succession. First, using 13 yearlong observations on vegetation and soil parameters in different successional stages, we show that the space‐for‐time substitution is valid for this chronosequence. We then quantify biomass changes for all dominant invertebrate and vertebrate species across all main trophic groups of plants and animals. All invertebrate and vertebrate species were assigned to a trophic group according to feeding preference, and changes in trophic group abundance were quantified for seven different successional stages of the ecosystem. We found changes from a marine‐fueled, decomposer‐based (brown) food web in early stages to a more terrestrial, plant‐based, herbivore‐driven (green) food web in intermediate succession stages, and finally to a decomposer‐based, terrestrial‐driven food web in the latest stages. These changes were accompanied not only by an increase in live plant biomass and a leveling toward late succession but also by a constant increase in the amount of dead plant biomass over succession. Our results show that the structure and dynamics of salt marsh food webs cannot be understood except in light of vegetation succession, and vice versa.

Spatially Extended Habitat Modification by Intertidal Reef-Building Bivalves has Implications for Consumer-Resource Interactions - Els M. van der Zee; Tjisse van der Heide; Serena Donadi; Johan S. Eklöf; Britas Klemens Eriksson; Han Olff; Henk W. van der Veer; Theunis Piersma (Ecosystems, 2012)

Comparative changes in density and demography of large herbivores in the Masai Mara Reserve and its surrounding human-dominated pastoral ranches in Kenya - Nina Bhola; Joseph O. Ogutu; Hans-Peter Piepho; Mohamed Y. Said; Robin S. Reid; N. Thompson Hobbs; Han Olff (Biodiversity and Conservation, 2012)

Managing invasions at the cost of native habitat? An experimental test of the impact of fire on the invasion of Chromolaena odorata in a South African savanna - Mariska te Beest; Joris P. G. M. Cromsigt; Johan Ngobese; Han Olff (Biological Invasions, 2012)

Large grazers modify effects of aboveground–belowground interactions on small-scale plant community composition - G. F. Veen; Elzemiek Geuverink; Han Olff (Oecologia, 2012)

Effects of Erosion from Mounds of Different Termite Genera on Distinct Functional Grassland Types in an African Savannah - Cleo M. Gosling; Joris P. G. M. Cromsigt; Nokukhanya Mpanza; Han Olff (Ecosystems, 2012)

Major Changes in the Ecology of the Wadden Sea: Human Impacts, Ecosystem Engineering and Sediment Dynamics - Britas Klemens Eriksson; Tjisse van der Heide; Johan van de Koppel; Theunis Piersma; Henk W. van der Veer; Han Olff (Ecosystems, 2010)

Landscape‐scale analyses suggest both nutrient and antipredator advantages to Serengeti herbivore hotspots - T. Michael Anderson; J. Grant C. Hopcraft; Stephanie Eby; Mark Ritchie; James B. Grace; Han Olff (Ecology, 2010)
Mechanistic explanations of herbivore spatial distribution have focused largely on either resource‐related (bottom‐up) or predation‐related (top‐down) factors. We studied direct and indirect influences on the spatial distributions of Serengeti herbivore hotspots, defined as temporally stable areas inhabited by mixed herds of resident grazers. Remote sensing and variation in landscape features were first used to create a map of the spatial distribution of hotspots, which was tested for accuracy against an independent data set of herbivore observations. Subsequently, we applied structural equation modeling to data on soil fertility and plant quality and quantity across a range of sites. We found that hotspots in Serengeti occur in areas that are relatively flat and located away from rivers, sites where ungulates are less susceptible to predation. Further, hotspots tend to occur in areas where hydrology and rainfall create conditions of relatively low‐standing plant biomass, which, coupled with grazing, increases forage quality while decreasing predation risk. Low‐standing biomass and higher leaf concentrations of N, Na, and Mg were strong direct predictors of hotspot occurrence. Soil fertility had indirect effects on hotspot occurrence by promoting leaf Na and Mg. The results indicate that landscape features contribute in direct and indirect ways to influence the spatial distribution of hotspots and that the best models incorporated both resource‐ and predation‐related factors. Our study highlights the collective and simultaneous role of bottom‐up and top‐down factors in determining ungulate spatial distributions.

Vertebrate herbivores influence soil nematodes by modifying plant communities - G. F. (Ciska) Veen; Han Olff; Henk Duyts; Wim H. van der Putten (Ecology, 2010)
Abiotic soil properties, plant community composition, and herbivory all have been reported as important factors influencing the composition of soil communities. However, most studies thus far have considered these factors in isolation, whereas they strongly interact in the field. Here, we study how grazing by vertebrate herbivores influences the soil nematode community composition of a floodplain grassland while we account for effects of grazing on plant community composition and abiotic soil properties. Nematodes are the most ubiquitous invertebrates in the soil. They include a variety of feeding types, ranging from microbial feeders to herbivores and carnivores, and they perform key functions in soil food webs. Our hypothesis was that grazing affects nematode community structure and composition through altering plant community structure and composition. Alternatively, we tested whether the effects of grazing may, directly or indirectly, run via changes in soil abiotic properties. We used a long‐term field experiment containing plots with and without vertebrate grazers (cattle and rabbits). We compared plant and nematode community structure and composition, as well as a number of key soil abiotic properties, and we applied structural equation modeling to investigate four possible pathways by which grazing may change nematode community composition. Aboveground grazing increased plant species richness and reduced both plant and nematode community heterogeneity. There was a positive relationship between plant and nematode diversity indices. Grazing decreased the number of bacterial‐feeding nematodes, indicating that in these grasslands, top‐down control of plant production by grazing leads to bottom‐up control in the basal part of the bacterial channel of the soil food web. According to the structural equation model, grazing had a strong effect on soil abiotic properties and plant community composition, whereas plant community composition was the main determinant of nematode community composition. Other pathways, which assumed that grazing influenced nematode community composition by inducing changes in soil abiotic properties, did not significantly explain variation in nematode community composition. We conclude that grazing‐induced changes in nematode community composition mainly operated via changes in plant community composition. Influences of vertebrate grazers on soil nematodes through modification of abiotic soil properties were of less importance.

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Monitoring large herbivore diversity at different scales: comparing direct and indirect methods - Joris P. G. M. Cromsigt; Susan J. van Rensburg; Rampal S. Etienne; Han Olff (Biodiversity and Conservation, 2009)

Interacting effects of grass height and herbivores on the establishment of an encroaching savanna shrub - Nicole Hagenah; Helena Munkert; Karin Gerhardt; Han Olff (Plant Ecology, 2009)

Herbivore impact on grassland plant diversity depends on habitat productivity and herbivore size - Elisabeth S. Bakker; Mark E. Ritchie; Han Olff; Daniel G. Milchunas; Johannes M. H. Knops (Ecology Letters, 2006)
Mammalian herbivores can have pronounced effects on plant diversity but are currently declining in many productive ecosystems through direct extirpation, habitat loss and fragmentation, while being simultaneously introduced as livestock in other, often unproductive, ecosystems that lacked such species during recent evolutionary times. The biodiversity consequences of these changes are still poorly understood. We experimentally separated the effects of primary productivity and herbivores of different body size on plant species richness across a 10‐fold productivity gradient using a 7‐year field experiment at seven grassland sites in North America and Europe. We show that assemblages including large herbivores increased plant diversity at higher productivity but decreased diversity at low productivity, while small herbivores did not have consistent effects along the productivity gradient. The recognition of these large‐scale, cross‐site patterns in herbivore effects is important for the development of appropriate biodiversity conservation strategies.

Confronting different models of community structure to species‐abundance data: a Bayesian model comparison - Rampal S. Etienne; Han Olff (Ecology Letters, 2005)
Species abundances are undoubtedly the most widely available macroecological data, but can we use them to distinguish among several models of community structure? Here we present a Bayesian analysis of species‐abundance data that yields a full joint probability distribution of each model's parameters plus a relatively parameter‐independent criterion, the posterior Bayes factor, to compare these models. We illustrate our approach by comparing three classical distributions: the zero‐sum multinomial (ZSM) distribution, based on Hubbell's neutral model, the multivariate Poisson lognormal distribution (MPLN), based on niche arguments, and the discrete broken stick (DBS) distribution, based on MacArthur's broken stick model. We give explicit formulas for the probability of observing a particular species‐abundance data set in each model, and argue that conditioning on both sample size and species count is needed to allow comparisons between the two distributions. We apply our approach to two neotropical communities (trees, fish). We find that DBS is largely inferior to ZSM and MPLN for both communities. The tree data do not allow discrimination between ZSM and MPLN, but for the fish data ZSM (neutral model) overwhelmingly outperforms MPLN (niche model), suggesting that dispersal plays a previously underestimated role in structuring tropical freshwater fish communities. We advocate this approach for identifying the relative importance of dispersal and niche‐partitioning in determining diversity of different ecological groups of species under different environmental conditions.

A novel genealogical approach to neutral biodiversity theory - Rampal S. Etienne; Han Olff (Ecology Letters, 2004)
Current neutral theory in community ecology views local biodiversity as a result of the interplay between speciation, extinction and immigration. Simulations and a mean‐field approximation have been used to study this neutral theory. As simulations have limitations of convergence and the mean‐field approximation ignores dependencies between species’ abundances when applied to species‐abundance data, there is still no final conclusion whether the neutral theory or the traditional lognormal model describes community structure best. We present a novel analytical framework, based on the genealogy of individuals in the local community, to overcome the problems of previous approaches, and show, using Bayesian statistics, that the lognormal model provides a slightly better fit to the species‐abundance distribution of a much‐discussed tropical tree community. A key feature of our approach is that it shows the tight link between genetic and species diversity, which creates important perspectives to future integration of evolutionary and community ecological theory.

The pristine rain forest? Remnants of historical human impacts on current tree species composition and diversity - Barend S. van Gemerden; Han Olff; Marc P.E. Parren; Frans Bongers (Journal of Biogeography, 2003)
Aim Tropical rain forests are often regarded as pristine and undisturbed by humans. In Central Africa, community‐wide disturbances by natural causes are rare and therefore current theory predicts that natural gap phase dynamics structure tree species composition and diversity. However, the dominant tree species in many African forests recruit poorly, despite the presence of gaps. To explain this, we studied the disturbance history of a species‐rich and structurally complex rain forest. Location Lowland rain forest in Southern Cameroon. Methods We identified the recruitment conditions of trees in different diameter classes in 16 ha of species‐rich and structurally complex ‘old growth’ rain forest. For the identification of recruitment preference we used independent data on the species composition along a disturbance gradient, ranging from shifting cultivation fields (representing large‐scale disturbance), to canopy gaps and old growth forest. Results In nine of sixteen 1‐ha forest plots the older trees preferred shifting cultivation fields for recruitment while younger trees preferred gaps and closed forest conditions. This indicates that these nine sites once experienced large‐scale disturbances. Three lines of evidence suggest that historical agricultural use is the most likely disturbance factor: (1) size of disturbed and undisturbed patches, (2) distribution of charcoal and (3) historical accounts of human population densities. Main conclusions Present‐day tree species composition of a structurally complex and species‐rich Central African rain forest still echoes historical disturbances, most probably caused by human land use between three to four centuries ago. Human impact on African rain forest is therefore, contrary to common belief, an issue not of the last decades only. Insights in historical use will help to get a more balanced view of the ‘pristine rain forest’, acknowledging that the dualism between ‘old growth’ and ‘secondary’ forest may be less clear than previously thought.

Recovery of conservation values in Central African rain forest after logging and shifting cultivation - Barend S. Van Gemerden; Gideon N. Shu; Han Olff (Biodiversity and Conservation, 2003)

Biomass partitioning, architecture and turnover of six herbaceous species from habitats with different nutrient supply - Peter Schippers; Han Olff (Plant Ecology, 2000)

Multiscale soil and vegetation patchiness along a gradient of herbivore impact in a semi-arid grazing system in West Africa - Max Rietkerk; Pieter Ketner; Joep Burger; Bart Hoorens; Han Olff (Plant Ecology, 2000)

Competition and facilitation in multispecies plant‐herbivore systems of productive environments - Jef Huisman; Han Olff (Ecology Letters, 1998)
We develop a multispecies plant‐herbivore model to explore how plant competition for light and the selectivity of herbivores affect abundance patterns of plants and herbivores along productivity gradients. The model considers a small and a tall plant species, a generalist herbivore, and a selective herbivore. The selective herbivore feeds only on the small plant species. In the absence of the generalist herbivore, the tall plant species becomes increasingly dominant with increasing productivity, and the small plant and its selective herbivore disappear. The model shows that generalist herbivores can facilitate selective herbivores by suppressing competition for light. This favours the small plant species, and thereby the selective herbivores. The model predictions are qualitatively consistent with field studies of multispecies plant‐herbivore systems.